The association between saliva control, silent saliva penetration, aspiration, and videofluoroscopic findings in Parkinson′s disease patients - Ali Rajaei; Fereshteh Ashtari; Seyed Abolfazl Azargoon; Ahmad Chitsaz; Mohammad Hussein Nilforoush; Masoud Taheri; Saba Sadeghi (Advanced Biomedical Research, 2015)
Background: Dysphagia is a common disorder among patients with Parkinson′s disease (PD). It occurs in up to 80% of all (PD) patients during the early stages of the disease and up to 95% in the advanced stages; but professionals may not hear from the patients about dysphagia symptoms until these symptoms reach an advanced stage and lead to medical complications. Materials and Methods: Thirty-three PD patients (mean age 66.09 ± 9.4 years; 24 men, nine women) participated in this study at our Neurology Institute, between April 20, 2013, and October 26, 2013. They were asked two questions; one about saliva control and the other about silent saliva penetration and aspiration. Next, they underwent the videofluoroscopic swallowing study (VFSS). Results: The Pearson Correlation coefficient between the Penetration-Aspiration Scale (PAS) scores and question 1 scores was 0.48 (P < 0.05, =0.25), and there was a significant correlation between the PAS scores and question 2 scores, and also question 1 scores + question 2 scores (r = 0.589, P < 0.05, =0 and r = 0589, P < 0.05, =0). Conclusions: This study showed a significant correlation between the questions about saliva control, silent saliva penetration, and aspiration, and laryngeal penetration and aspiration during VFSS. Therefore, by using these two questions, the potential silent laryngeal penetration and aspiration during meals could be detected before it led to aspiration pneumonia. Taking the benefit of these questions, as a part of the swallowing assessment of PD patients, is recommended.